The Hundreds - Berlant, Lauren; Stewart, Kathleen (Duke University Press, 2019)
In The Hundreds Lauren Berlant and Kathleen Stewart speculate on writing, affect, politics, and attention to processes of world-making. The experiment of the one hundred word constraint-each piece is one hundred or multiples of one hundred words long-amplifies the resonance of things that are happening in atmospheres, rhythms of encounter, and scenes that shift the social and conceptual ground. What's an encounter with anything once it's seen as an incitement to composition? What's a concept or a theory if they're no longer seen as a truth effect, but a training in absorption, attention, and framing? The Hundreds includes four indexes in which Andrew Causey, Susan Lepselter, Fred Moten, and Stephen Muecke each respond with their own compositional, conceptual, and formal staging of the worlds of the book